Socioeconomic determinants of chronic health diseases among older Indian adults: a nationally representative cross-sectional multilevel study - Lucky Singh; Prashant Kumar Singh; Ravi Mehrotra; Ritam Dubey; Shalini Singh (BMJ Open)
Objective Study uses multilevel modelling to examine the effect of individual, household and contextual characteristics on chronic diseases among older Indian adults.Design Nationally representative cross-sectional study.Participants Data from the nationally representative, India Human Development Survey conducted in 2011–2012 was used in this study. The survey asked information related to the diagnosed chronic illnesses such as cataract, tuberculosis, hypertension, heart disease and others. The sample size of this study comprised 39 493 individuals who belonged to the age group 50 years and above.Measures Self-reported diagnosed chronic illness.Method Considering the hierarchal structure of the data multilevel logistic regression analysis was applied to attain the study objective.Results Older adults aged 80 years and older were found with three times more chances (OR: 3.99, 95% CI 2.91 to 5.48) of suffering from a chronic ailment than 50–54 years old. Lifestyle risk factors such as alcohol and tobacco (smoked and smokeless) consumption were noted to be significantly associated with the presence of chronic illness whereas older adults who have never consumed smokeless tobacco stood 20% fewer chances (OR: 0.80, 95% CI 0.68 to 0.94) of having any chronic illness. Contextual level variables such as older adults residing in the rural areas were found with 17% fewer chances (OR: 0.83, 95% CI 0.70 to 0.97) of suffering from a chronic illness.Conclusion Even after controlling for various characteristics at the individual, household and contextual levels, significant variations in chronic illness remain unexplained at the community and state level, respectively. The findings of this study could effectively be utilised to consider more contextual variables to examine the chronic health status among the growing older population of India.